Pengaruh Durasi Penyimpanan Dexlite Terhadap Penurunan Tekanan Dan Endapan Pada Fuel Filter Bahan Bakar - Sibarani, Jeico Mauro; Ghurri, Ainul; Wirawan, I Ketut Gede (Teknik Desain Mekanika; Vol 10 No 4 (2022): Oktober 2022 : Teknik Desain Mekanika, 2022)
Abstract Biodiesel is an alternative energy that can be used as a substitute for diesel oil as fuel for diesel engines. Biodiesel has advantages as an alternative energy. Its function can be used in various countries, biodiesel production also helps economic growth in Indonesia in terms of export-import. However, some of the advantages of using biodiesel are that it is not dangerous and can be decomposed by the environment so that it becomes an alternative environmentally friendly diesel fuel, does not contain harmful chemicals such as sulfur which is not good for the environment, biodiesel can also be used as a substitute for oil/lubricant in engines. The purpose of this study was to examine the effect of variations in the duration of dexlite storage on pressure drops and deposits on the fuel filter. This test was carried out with 400 liters of fuel flowing through the fuel filter by varying the dexlite storage duration below 40 hours, above 40 hours, above 72 hours, and above 96 hours. The initial fuel pressure is set at 105 kPa before entering the fuel filter. The test results show that variations in the duration of dexlite storage affect the blockage of the fuel filter. The longer the duration of storage of dexlite causes the fuel filter to become clogged more easily. Dexlite testing over 96 hours showed the highest pressure drop was 40 kPa and the sediment that occurred was 174.79 grams. Keywords: Dexlite, Fuel Filter, Biodiesel, Pressure Drop, Sediment